Науково-методологічні засади сучасного краєзнавства - Реєнт, О. (Краєзнавство, 2017)
У статті розглядається актуальність та необхідність формування дисципліноформуючого
статусу краєзнавства як сучасної наукової дисципліни. The article represents the urgency and necessity of acknowledging local history as a modern scientific
subject. The methodological basis of local history researches are scientific approaches and principles
which are generally accepted in the science to cognize the processes of nature and society development,
such as scientific and historical character, complexity and systematic character. Being based on these universal
principles of scientific cognition, local history should not only improvein current situation, but, in
fact, it should rather re-build its own theoretical and methodological foundation. When it comes to the
methodology of local history studies, the following traditional methods which are typical to these studiesare
usually called: literature review, mapping, field observation method, visual method, questionnaire, etc.
They are used in the majority of the local history researches at the micro level. Of course, they are important
to local history and are often practiced. At the same time, their use should be improvedboth in local history
studies and in the related disciplines, taking account their achievements. However, today due to the emphasis
on the advanced interpretation of the object-subject area of local history studies, there is an urgent
need for research testing methods at meso- and macro-levels. В статье рассматривается актуальность и необходимость формирования дисциплинофор-
мирующего статуса краеведения как современной научной дисциплины.